Preserving Ethnic Identity among Tribal Communities in Ladakh: Balancing Cultural Heritage and Sustainable Development - Khan, Jaffar Ali (Journal of Ecohumanism, 2025)
Ladakh is a cold desert UT established in 2019, which provides interesting grounds for examining the preservation of identity alongside development problems among the tribal population. According to the census of 2011, the total population of Ladakh amounts to 274,289, of whom 218,193 belong to Schedule Tribes (STs), accounting for 79.54 per cent of the total population. As can be seen from the Centre for Policy Studies’ report, there is a considerable shift in demographic structure in the recent ten years, since the proportion of ST population has declined from 85.2 per cent in 2001 to less than 80 per cent in 2011. Hence, it is necessary to investigate the socio-cultural features of such communities, since their languages, Buddhist monastic culture, Balti Islamic culture, and pastoral economy are closely associated with the fragile Himalayan environment. Field ethnobotanical studies conducted in the Balti, Beda, and Brokpa populations during 2020–2025, which comprised 20 structured interviews and it demonstrate the application of traditional botanical knowledge for securing food and health as well as supporting livelihoods in the course of the modernisation process with tourism and infrastructure development in this region. According to the research paper, the sustainable development strategies for Ladakh should be associated with community-based conservation programs, culture-based educational policies, and ecological security measures without taking them as conflicting issues. Using the information obtained in the Census, Tribal Research Institute directives, and contemporary scholarly surveys, this abstract reflects the role of Ladakh in the context of tribal policy in India as a whole, where ethnic legacy protection and development of tribes become one and the same problem.